Assessing acute myeloid leukemia susceptibility in rearrangement‐driven patients by DNA breakage at topoisomerase II and CCCTC‐binding factor/cohesin binding sites. Issue 12 (26th August 2021) - Atkin, Naomi D.; Raimer, Heather M.; Wang, Zhenjia; Zang, Chongzhi; Wang, Yuh‐Hwa
Abstract: An initiating DNA double strand break (DSB) event precedes the formation of cancer‐driven chromosomal abnormalities, such as gene rearrangements. Therefore, measuring DNA breaks at rearrangement‐participating regions can provide a unique tool to identify and characterize susceptible individuals. Here, we developed a highly sensitive and low‐input DNA break mapping method, the first of its kind for patient samples. We then measured genome‐wide DNA breakage in normal cells of acute myeloid leukemia (AML) patients with KMT2A (previously MLL ) rearrangements, compared to that of nonfusion AML individuals, as a means to evaluate individual susceptibility to gene rearrangements. DNA breakage at the KMT2A gene region was significantly greater in fusion‐driven remission individuals, as compared to nonfusion individuals. Moreover, we identified select topoisomerase II (TOP2)‐sensitive and CCCTC‐binding factor (CTCF)/cohesin‐binding sites with preferential DNA breakage in fusion‐driven patients. Importantly, measuring DSBs at these sites, in addition to the KMT2A gene region, provided greater predictive power when assessing individual break susceptibility. We also demonstrated that low‐dose etoposide exposure further elevated DNA breakage at these regions in fusion‐driven AML patients, but not in nonfusion patients, indicating that these sites are preferentially sensitive to TOP2 activity in fusion‐driven AML patients. These results support that mapping of DSBs in patients enables discovery of novel break‐prone regions and monitoring of individuals susceptible to chromosomal abnormalities, and thus cancer. This will build the foundation for early detection of cancer‐susceptible individuals, as well as those preferentially susceptible to therapy‐related malignancies caused by treatment with TOP2 poisons.